2018
DOI: 10.1007/s11912-018-0657-2
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for the Management of Cancer Treatment-Related Toxicities

Abstract: Purpose of Review To (1) explain what yoga is, (2) summarize published literature on the efficacy of yoga for managing cancer treatment-related toxicities, (3) provide clinical recommendations on the use of yoga for oncology professionals, and (4) suggest promising areas for future research. Recent Findings Based on a total of 24 phase II and one phase III clinical trials, low-intensity forms of yoga, specifically gentle hatha and restorative, are feasible, safe, and effective for treating sleep disruption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 70 publications
(181 reference statements)
1
39
0
Order By: Relevance
“…Overall, the results of the study are predominantly in line with the results of more recent meta-analyses, which could only find small to medium effect sizes through yoga therapy regarding fatigue [29]. At this point, it is important to note that a yoga therapy with only 8 1-h sessions is a rather short and small intervention.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the results of the study are predominantly in line with the results of more recent meta-analyses, which could only find small to medium effect sizes through yoga therapy regarding fatigue [29]. At this point, it is important to note that a yoga therapy with only 8 1-h sessions is a rather short and small intervention.…”
Section: Discussionsupporting
confidence: 84%
“…Yoga is increasingly recognized as a complementary approach to diminishing the onset and severity of cancer‐related symptoms and/or treating such symptoms (Fig. ) . Research has demonstrated the feasibility and acceptability of yoga among patients with cancer who are undergoing treatment and those who have transitioned out of the medical setting .…”
Section: Introductionmentioning
confidence: 99%
“…1). 14 Research has demonstrated the feasibility and acceptability of yoga among patients with cancer who are undergoing treatment and those who have transitioned out of the medical setting. [15][16][17] Most National Cancer Institute-designated comprehensive cancer centers now include information about yoga on their websites (87%) and offer on-site yoga instruction (69%).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of posttreatment yoga as a treatment for fatigue, 24 phase II and 1 phase III trials were reviewed, demonstrating that yoga is safe and effective in treating cancer-related fatigue. 22 However, yoga type and frequency varied widely among the 24 studies, samples were small, and bias was evident. Further, the need to develop prescriptive guidelines for yoga was identified.…”
Section: Self-management Interventionsmentioning
confidence: 99%